2019
DOI: 10.1021/acs.chemmater.9b02074
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Dissolution of Vanadium from Cation-Disordered Li2–xVO2F via a Concentrated Electrolyte Approach

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…To elucidate the mechanism responsible for the improved cycling stability of VS 4 in the high-concentration and localized high-concentration electrolytes, we investigated the dissolution of V from the VS 4 cathode during cycling. Several studies have shown that the capacity fading of transition metal-based cathodes is associated with the dissolution of the transition metal from the cathode material, which leads to the loss and degradation of the active material, along with an increase in the internal resistance. For V-based cathodes, such as V 2 O 5 and Li 2– x VO 2 F, the dissolution of V is one of the primary reasons for their poor cycling stability. We determined that the color of the separators changed after the discharge/charge cycling in the VS 4 |Li half-cells with the 1.2 M LiFSI/EC:PC electrolyte. The separators turned reddish after 100 cycles in the 1.2 M LiFSI/EC:PC electrolyte; however, the color of the cycled separators did not change in 3.2 M LiFSI/EC:PC and 1.9 M LiFSI/EC:PC:HFE electrolytes (Figure a).…”
Section: Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…To elucidate the mechanism responsible for the improved cycling stability of VS 4 in the high-concentration and localized high-concentration electrolytes, we investigated the dissolution of V from the VS 4 cathode during cycling. Several studies have shown that the capacity fading of transition metal-based cathodes is associated with the dissolution of the transition metal from the cathode material, which leads to the loss and degradation of the active material, along with an increase in the internal resistance. For V-based cathodes, such as V 2 O 5 and Li 2– x VO 2 F, the dissolution of V is one of the primary reasons for their poor cycling stability. We determined that the color of the separators changed after the discharge/charge cycling in the VS 4 |Li half-cells with the 1.2 M LiFSI/EC:PC electrolyte. The separators turned reddish after 100 cycles in the 1.2 M LiFSI/EC:PC electrolyte; however, the color of the cycled separators did not change in 3.2 M LiFSI/EC:PC and 1.9 M LiFSI/EC:PC:HFE electrolytes (Figure a).…”
Section: Results and Discussionmentioning
confidence: 98%
“…Studies have shown that the reasons for capacity fading should be the degradation of VS 4 with the accumulation of insulating Li 2 S ,, and the formation of a resistive film on the VS 4 surface owing to electrolyte decomposition . The poor cycling stability of VS 4 may also be associated with dissolution of V from the active material, which results in the degradation of VS 4 during cycling, as has been observed in the cathodes of other V-based materials such as V 2 O 5 , and Li 2– x VO 2 F …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The deficiency of being less electronically reactive poses a significant barrier for V-compounds to fully claim their theoretical energy and power density. Another major issue of V-compounds is associated with the amphiprotic nature of vanadium, where deleterious interfacial reaction between the electrolyte (strong Lewis acid) and vanadium through acid–base interaction exacerbates its dissolution problem . As a result, the catalytic decomposition of the electrolyte can trigger rapid capacity fading due to the loss of active materials.…”
Section: Introductionmentioning
confidence: 99%
“…Another major issue of V-compounds is associated with the amphiprotic nature of vanadium, where deleterious interfacial reaction between the electrolyte (strong Lewis acid) and vanadium through acid−base interaction exacerbates its dissolution problem. 5 As a result, the catalytic decomposition of the electrolyte can trigger rapid capacity fading due to the loss of active materials. The moderate toxicity of vanadium is one of the concerns that should not be overlooked.…”
Section: Introductionmentioning
confidence: 99%